A characterisation of living language in spoken and written Chinese language - Gui, Qianyao; Cui, Yuyue; Zhang, Wenwei; Shi, Mingxuan; Feng, Yunbo (Transactions on Social Science, Education and Humanities Research, 2024)
This paper analyses the features of living language in spoken and written Chinese. By comparing the characteristics of spoken and written Chinese, the mechanism of generation and manifestation of activated language are explored. It is found that spoken Chinese has a strong variability, flexibility and real-time nature, which is manifested in such features as lexical diversity, grammatical simplification and omission, and phonological variation specific to spoken language. Written Chinese, on the other hand, is more standardised and stable, focusing on accuracy and normality, manifested in rigorous grammatical structure, fixed vocabulary usage and formal tone. These features of living language correspond to different language needs and communication purposes in the use of spoken and written language. Therefore, it is important to understand and master the features of modalised language in order to improve the expressive ability of spoken and written Chinese.